Stable carbon and nitrogen isotopes in shells organic matrix of alien mollusk Viviparus viviparus (Linnaeus, 1758) from the Novosibirsk reservoir - Yanygina, L. V.; Volgina, D.D. (Acta Biologica Sibirica, 2019)
Analysis of stable carbon and nitrogen isotopes is widely used in environmental studies for exploring the structure of trophic networks, assess the role of various resources in the nutrition of individual specimens and determine the trophic level of consumers. The shell grows steadily over the lifetime of the mollusc and reflects the nutritional characteristics of individuals at different ages. Stable carbon and nitrogen isotopes in shells of alien mollusks Viviparus viviparus (Linnaeus, 1758) collected in the Novosibirsk reservoir were examined in this study. Statistically significant differences in isotopic composition of shell fragments corresponding to annual growth in different years were noted. The assumption was made about significant role of interannual differences in trophic conditions of the reservoir in the formation of the isotopic signature of mollusk shells. The results of this work can be used in environmental and paleolimnological studies of mollusk nutrition, in the reconstruction of long-term changes in the ecological conditions of water bodies.